(untitled) (Journal of Surgical Sciences, 2019)
Background: Breast cancer is the most common cancer of Bangladeshi women. Almost allpresent with palpable lump and 40% of them are with locally advanced breast cancer.Neoadjuvant chemotherapy is the standard choice of treatment for the patients. Objective: To observe the clinical and pathological response of locally advanced breastcancer after four cycles of chemotherapy and surgery. Methods: This prospective study was carred over the newly diagnosed locally advancedbreast cancer (LABC) patients from January 2010 to December 2014. Before going toneoadjuvant chemotherapy each patient was evaluated clinically, radiologically and withother relevant investigations. The size of primary tumor and axillary node was measured andrecorded. Chemotherapy schedule with Cyclophosphamide 600mg/m2 and Doxorubicin60mg/m2 (AC) and compared with the previous record. After 3-4 weeks of completion ofchemotherapy, the patients was prescribed and carried out three weekly for four cycles.Primary tumor size and axillary nodal size was measured who were undergone mastectomyand axillary dissection. Histopathology was done to see then the pathological response ofprimary tumor and axillary node. Other biological marker such as estrogen receptor (ER),progesterone receptor (PR) and Human epidermal growth receptor (HER-2) was done. Aftercompletion of study the data was compiled and analyzed. Results: Total 220 cases of LABC were enrolled in this study. After four cycles of chemotherapywith AC, 194 patients (88%) responded clinically, 29 patients (13%) showedcomplete clinical response (cCr)-and 165 patients (75%) partial response (pCr). Surgicalspecimen showed complete pathological response (cPr) in 22 patients (10%). Conclusion: Neoadjuvant chemotherapy with AC is the standard chemotherapy schedule forlocally advanced breast cancer and radical surgery was possible in 75% of the patients. Journal of Surgical Sciences (2016) Vol. 20 (1) : 13-17